2013
DOI: 10.5858/arpa.2013-0253-cr
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Profundus (Panniculitis): A Potential Mimic of Subcutaneous Panniculitis-like T-Cell Lymphoma

Abstract: Lupus profundus is a rare manifestation of cutaneous lupus erythematosus, seen in 1% to 3% of patients. It most commonly presents in association with classic chronic cutaneous lesions of discoid lupus erythematosus; however, such lesions, as well as a clinical history of lupus erythematosus, may be lacking. The differential diagnosis for lymphocytic lobular panniculitides is broad; however, the consideration of subcutaneous panniculitis-like T-cell lymphoma is most critical. Recently, there have been several r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 16 publications
1
32
0
4
Order By: Relevance
“…Histopathological criteria favoring LEP include epidermal and dermal changes of LE, dermal mucin deposition, lymphoid follicles with reactive germinal centers, mixed cell infiltrate with prominent plasma cells, plasmacytoid dendritic cells, hyaline or lipomembranous fat necrosis and polyclonal TCR-U gene rearrangement. 10,[19][20][21][22] Histopathological criteria favoring SPTL include moderate to marked nuclear atypia with adipocyte rimming with a fat necrosis pattern that is more probably to be fibrinoid or coagulative. 10,19 Our study found some overlapping features of SPTL with LEP including vacuolar alteration, periadnexal involvement, and prominent plasma cells.…”
Section: Three Random Skin Biopsies (From Both Inner Thighs and Abdomen)mentioning
confidence: 99%
“…Histopathological criteria favoring LEP include epidermal and dermal changes of LE, dermal mucin deposition, lymphoid follicles with reactive germinal centers, mixed cell infiltrate with prominent plasma cells, plasmacytoid dendritic cells, hyaline or lipomembranous fat necrosis and polyclonal TCR-U gene rearrangement. 10,[19][20][21][22] Histopathological criteria favoring SPTL include moderate to marked nuclear atypia with adipocyte rimming with a fat necrosis pattern that is more probably to be fibrinoid or coagulative. 10,19 Our study found some overlapping features of SPTL with LEP including vacuolar alteration, periadnexal involvement, and prominent plasma cells.…”
Section: Three Random Skin Biopsies (From Both Inner Thighs and Abdomen)mentioning
confidence: 99%
“…A variety of diseases, especially dermatological and rheumatic conditions, may have an appearance and presentation similar to SPTL. These include conditions such as septal panniculitis (erythema nodosum), lobular panniculitides (erythema induratum, nodular vasculitis, and lupus panniculitis), lobular and septal panniculitis (alpha-1 antitrypsin deficiency panniculitis), infectious panniculitis, pyoderma gangrenosum, systemic vasculitis and inflammatory myopathies [2][3][4][5]. Histopathologic examination shows subcutaneous infiltrates containing a mixture of neoplastic pleomorphic cells of varying sizes and macrophages and rimming of individual fat cells by neoplastic cells are features of SPTL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The distinction is based on routine histology, immunofluorescence, and serology. The particularly troublesome differential diagnosis is SPTCL (Arps and Patel, 2013). …”
Section: Diagnosis and Differential Diagnosismentioning
confidence: 99%